Fewer fixations of longer duration? Expert gaze behavior revisited - Klostermann, A.; Moeinirad, S. (German Journal of Exercise and Sport Research, 2020)
In the current study, we investigated gaze behavior in sports by reviewing expertise-related differences in fixation duration, number of fixations, gaze location, and quiet eye duration. The review was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines and included a total of 101 studies. Applying the vote-counting procedure, differences in gaze variables were aggregated as a function of the total number and the publication year. Moreover, for fixation duration and number of fixations an effect-size analysis was conducted. For gaze location and quiet eye duration, different gaze behavior in experts was found, in particular, when compared to novices. However, for fixation duration and number of fixations the results were less clear. Overall, there were more studies with nonsignificant results than studies with significant (positive and negative) results. These findings were confirmed by the effect-size analysis with average effect sizes in 2017 being small or just above the null effect (fixation duration: d = 0.21; number of fixations: d = 0.01). There was only minor mediation by the factors representativeness of the experimental design, type of sports, and type of task. Overall, the findings suggest that the empirical evidence on expertise-related differences in gaze behavior declined in recent years. Rather, the expert advantage in cognitive and motor tasks might be better explained with an optimal perception-action coupling.